Development of ready-to-drink chocolate eh - Ng, Giselle U.; Francisco, Ma. Leonora dL. (c2011.)
ABSTRACT This study aimed to develop a ready-to-drink (RTD) chocolate eh. Consumer (n=52) preference, acceptance and intensity ratings were done to determine which type of tablea- fermented or unfermented- the Filipino palate prefer for a RTD chocolate eh. Sensory results showed that tablea made from unfermented tablea was more preferred and received an overall acceptability rating equivalent to "like slightly". To determine optimum formulation, a 3x3 full factorial design was used where tablea (10,17,and 24%) and sugar (5,12,and 19%) concentrations were studied. The pH and lightness (L*) of the sample generally decreased as concentration of tablea and sugar increased, whereas the increase in total soluble solids, redness (+a*), and viscosity was directly proportional with tablea and sugar concentration. Prediction models were made from significant models at p<0.05. The optimum area, predicted to give hedonic ratings ≥ 6.2 for overall acceptance, color, aroma, chocolate flavor, sweetness, and bitterness and ≥ 5.8 for viscosity, was defined by formulating RTD chocolate eh with 13 to 14% tablea and 18.5 to 19% sugar. Contour plots for RTD chocolate eh showed that the acceptability of chocolate flavor and overall acceptability were linear in level of sugar, and both tablea and sugar concentrations affected the hedonic ratings of aroma, color, sweetness, bitterness, and viscosity. The effect of homogenization using colloid mill on the stability of RTD chocolate eh was also observed by measuring rate of creaming and sedimentation as a function of days on homogenized and sterilized, non-homogenized and sterilized, homogenized and non-sterilized, and non-homogenized and non-sterilized samples. Both sterilization and homogenization was found to have a delaying effect on the visual separation of RTD chocolated eh. Finally, non-homogenized and sterilized chocolate eh were found to be microbiologically safe. Availability of RTD chocolate eh in the market will not only promote the familiarity of the cultural Filipino drink in a contemporary setting but will also serve to provide an alternative nutritional and functional beverage for the Filipinos and a new demand for the cacao industry.
Thesis(BSFT)--University of the Philippines Diliman
Keywords: Chocolate drinks -- Philippines